2020
DOI: 10.1177/1078155220971024
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy problems and health related quality of life among patients with colorectal cancer in a Kenyan tertiary health facility

Abstract: Background Colorectal cancer is the third most common form of cancer in males and the second in females globally. The ill-health due to cancer and use of multiple therapies may result in drug related problems and also affect the health-related quality of life of the patients. Objective To characterize drug therapy problems and health-related quality of life among patients with colorectal cancer at Kenyatta National Hospital. Methodology: A descriptive prospective cross-sectional study design was used and simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…DDIs, ADRs, and the need for additional drug therapy were the most prevalent DRPs, which accounted for 32.7%, 32%, and 17%, respectively, in FHCSH. Similarly, a study in Kenya on CRC 21 and cervical cancer 30 patients reported that ADRs and DDIs were the most prevalent DRPs. In terms of severity, 58% of the DDIs were significant, necessitating modification or close monitoring of the drug interactions’ outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…DDIs, ADRs, and the need for additional drug therapy were the most prevalent DRPs, which accounted for 32.7%, 32%, and 17%, respectively, in FHCSH. Similarly, a study in Kenya on CRC 21 and cervical cancer 30 patients reported that ADRs and DDIs were the most prevalent DRPs. In terms of severity, 58% of the DDIs were significant, necessitating modification or close monitoring of the drug interactions’ outcomes.…”
Section: Discussionmentioning
confidence: 91%
“… 38 In the same manner, a study conducted among CRC patients at a Kenyan tertiary care facility reported that cardiovascular disease (39.4%) is the leading co-morbid medical illness. 21 About 22% of patients had co-existing complications, with anemia (30.3%) being the most common. Likewise, anemia is seen in approximately 30%–75% of CRC patients, 47 , 48 and is a predictor of prognosis for CRC patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations